Comparative Analysis of Teacher Perceptions and Strategies in Addressing Gender and Race-Based Bullying - Ismail, Liban (My University, 2024)
This research study focuses on teachers' perceptions and intervention strategies concerning identity-based bullying, including both ethnic and gender-based incidents in Russian schools. The study specifically investigates how teachers respond to various bullying scenarios that involve identity factors, such as ethnicity and gender/sexual minority. The research employs quantitative methodologies, analyzing responses from a sample of 103 teachers in Russia. Data were collected through questionnaires, focusing on teachers' ethnic backgrounds, cultural experiences, and professional training. The main findings revealed a connection between these factors and the teachers' chosen intervention strategies. By studying individual-level interventions in multicultural educational settings, this research contributes valuable insights to the field of anti-bullying research, aiding the development of evidence-based practices for addressing diverse forms of identity-based bullying. The findings from this study are critical for shaping future anti-bullying programs, and promoting safer, more inclusive, and equitable educational environments for students, irrespective of their cultural, ethnic, or gender identities.
Keywords: identity-based bullying, ethnic bullying, gender-based bullying, teachers' perceptions, intervention strategies, multicultural education, diverse primary schools.